If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5b + -17 + -1b = 7 Reorder the terms: -17 + 5b + -1b = 7 Combine like terms: 5b + -1b = 4b -17 + 4b = 7 Solving -17 + 4b = 7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 4b = 7 + 17 Combine like terms: -17 + 17 = 0 0 + 4b = 7 + 17 4b = 7 + 17 Combine like terms: 7 + 17 = 24 4b = 24 Divide each side by '4'. b = 6 Simplifying b = 6
| -2y+x+3y-x= | | x-4.14=x*.1 | | 3(n+2)=17 | | 4+2n=34 | | 9x=5x+640 | | -9=9+x | | x+100=74+93 | | 8(W+0.0022)= | | 5(x-1)+2x=6x-2 | | -(10)squared= | | [p-8]+6=15 | | 5x^2=-8x-5 | | x^2-6x+11=9 | | -10x+6x+4x= | | (x-2)(x-3)(2x+7)=0 | | 8x-15=-7x | | .3x+130000=x | | 8+2n=44 | | 1+7(-7k+5)=-111 | | v/7-8=1 | | 2(8.50)+3(5.50)=x | | -5-(15y-1)=2(7x-16)-y | | -30=5y | | 5x+26=3x+16 | | 4-3(2x+5)=x-2(3-x) | | w+2(w-6)=-6 | | 2-x-4=67+xx | | 8x+6=17x+6 | | 5-z=-10 | | 0=6t+2(1-4t) | | 8x-(3x-16)=51 | | cos^2(6x)=cos(12x) |